2013
DOI: 10.1063/1.4816665
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular theory for the phase equilibria and cluster distribution of associating fluids with small bond angles

Abstract: We develop a new theory for associating fluids with multiple association sites. The theory accounts for small bond angle effects such as steric hindrance, ring formation, and double bonding. The theory is validated against Monte Carlo simulations for the case of a fluid of patchy colloid particles with three patches and is found to be very accurate. Once validated, the theory is applied to study the phase diagram of a fluid composed of three patch colloids. It is found that bond angle has a significant effect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…It is also of interest as a network-forming fluid for its interesting phase behavior and analogies to water and other molecular fluids that form tetrahedral networks. 50,51,5759 This is the geometry considered throughout the first part of the work presented here.…”
Section: Introductionmentioning
confidence: 99%
“…It is also of interest as a network-forming fluid for its interesting phase behavior and analogies to water and other molecular fluids that form tetrahedral networks. 50,51,5759 This is the geometry considered throughout the first part of the work presented here.…”
Section: Introductionmentioning
confidence: 99%
“…For a sphere to be bonded, it must be in an orientation θ ≤ θc or θ ≥ π -θc. In the absence of an external field these two cases will occur with equal probability yielding the following ODF for bonded spheres (17) U(x) is the Heaviside step function. Note, Eq.…”
Section: Theorymentioning
confidence: 99%
“…Extensions beyond TPT1 have been the topic of much research in recent years. Kalyuzhnyi et al [29][30][31] and Marshall et al developed theory to include multiple bonds per site, [32][33][34][35][36][37] formation of cyclic structures of associated species, [38][39][40] and cooperative hydrogen bonding. 41,42 While the results of these theoretical studies have been confirmed by Monte Carlo simulation (MC), the primary motivation has been in modeling patchy colloids.…”
Section: Introductionmentioning
confidence: 99%